Impact of the law on the shaping of the agricultural system on the agricultural land lease - Suchoń, Aneta (Przegląd Prawa Rolnego, 2023)
The aim of the deliberations presented in the article was an attempt to determine to what extent and in what degree the Act on the shaping of the agricultural system influences the conclusion, execution and termination of agricultural land leases, and whether these regulations are conducive to a stable agricultural activity on the agricultural land leased. The subject of the analysis were the provisions contained in the Act of 11 April 2003 on the shaping of the agricultural system, the Civil Code and the Act of 19 October 1991 on the management of agricultural real estate of the State Treasury. The conclusions of the deliberations are that successive amendments to the Act on the shaping of the agricultural system have had an increasing impact on the conclusion, execution and termination of all types of agricultural land leases – private, municipal and state-owned. Many provisions, however, raise interpretational doubts. Hence the need to develop a law on agricultural lease seems justified. Currently however, in order to eliminate the doubts arising from the interpretation of the existing provisions and in order to ensure stable conditions for agricultural activity, the Act on the shaping of the agricultural system must be amended.